NRF1-mediated microglial activation triggers high-altitude cerebral edema. (15th June 2022) - Wang, Xueting; Chen, Guijuan; Wan, Baolan; Dong, Zhangji; Xue, Yan; Luo, Qianqian; Wang, Dan; Lu, Yapeng; Zhu, Li
Abstract: High-altitude cerebral edema (HACE) is a potentially fatal encephalopathy associated with a time-dependent exposure to the hypobaric hypoxia of altitude. The formation of HACE is affected by both vasogenic and cytotoxic edema. The over-activated microglia potentiate the damage of blood–brain barrier (BBB) and exacerbate cytotoxic edema. In light with the activation of microglia in HACE, we aimed to investigate whether the over-activated microglia were the key turning point of acute mountain sickness to HACE. In in vivo experiments, by exposing mice to hypobaric hypoxia (7000 m above sea level) to induce HACE model, we found that microglia were activated and migrated to blood vessels. Microglia depletion by PLX5622 obviously relieved brain edema. In in vitro experiments, we found that hypoxia induced cultured microglial activation, leading to the destruction of endothelial tight junction and astrocyte swelling. Up-regulated nuclear respiratory factor 1 (NRF1) accelerated pro-inflammatory factors through transcriptional regulation on nuclear factor kappa B p65 (NF-κB p65) and mitochondrial transcription factor A (TFAM) in activated microglia under hypoxia. NRF1 also up-regulated phagocytosis by transcriptional regulation on caveolin-1 (CAV-1) and adaptor-related protein complex 2 subunit beta (AP2B1). The present study reveals a new mechanism in HACE: hypoxia over-activates microglia through up-regulation of NRF1, which both induces inflammatory response through transcriptionally activating NF-κB p65 and TFAM, and enhances phagocytic function through up-regulation of CAV-1 and AP2B1; hypoxia-activated microglia destroy the integrity of BBB and release pro-inflammatory factors that eventually induce HACE.